Numerical simulation of the experimental results of a RC frame retrofitted with RC Infill walls - Kyriakides, Nicholas; Chrysostomou, Christis; Kotronis, Panagiotis; Georgiou, Elpida; Roussis, Panayiotis C. (My University, 2015)
The effectiveness of seismic retrofitting of RC-frame buildings by converting selected bays into new walls through infilling with RC walls was studied experimentally using a full-scale four-storey model tested with the pseudo-dynamic (PsD) method. The frames were designed and detailed for gravity loads only using different connection details between the walls and the bounding frame. In order to simulate the experimental response, two numerical models were formulated differing at the level of modelling. The purpose of this paper is to illustrate the capabilities of these models to simulate the experimental nonlinear behaviour of the tested RC building strengthened with RC infill walls and comment on their effectiveness. The comparison between the capacity, in terms of peak ground acceleration, of the strengthened frame and the one of the bare frame, which was obtained numerically, has shown a five-fold increase.
Keywords: Connection details; Fibre model; Finite element analysis; Pseudo-dynamic experimental results; RC infill walls; Retrofitting of RC buildings